The Influence of Tax Planning, Capital Structure and Sales Growth on Company Value - Nurmilah, Nurmilah; Saga, Baharuddin (Journal Of Accounting Management Business And International Research, 2025)
This study investigates the impact of tax planning, capital structure, and sales growth on the value of companies listed on the LQ45 index from 2018-2022. Company valuation, reflecting investor perception, is crucial as it predicts future performance and influences shareholder wealth. Tax planning aims to minimize tax liabilities, thereby enhancing net profit. Capital structure, comprising equity and debt, affects financial stability and company growth, while sales growth indicates market competitiveness and revenue potential. Using secondary data from the Indonesia Stock Exchange, this research employs quantitative analysis with EViews12. The hypotheses are tested through t-tests and F-tests. The findings reveal that tax planning and sales growth do not significantly affect company value, while capital structure negatively impacts it. However, when considered together, tax planning, capital structure, and sales growth significantly influence company value. These results highlight the importance of optimal financial management and strategic tax planning in enhancing company valuation and investor confidence. The study contributes to the literature by providing empirical evidence on the relationships between these financial strategies and company value in the Indonesian context.